Predictive Value of Neutrophil Lymphocyte Ratio and Platelet Lymphocyte Ratio in Immediate Outcomes of ST-elevation Myocardial Infarction: A Cross-sectional Study - Sadashiva, Sneha Barkur; Chenthil, KS (Journal of clinical and diagnostic research, 2021)
Introduction: There have been various inflammatory markers implicated in the pathogenesis of Acute Coronary Syndromes (ACS). However, the role of the Neutrophil Lymphocyte Ratio (NLR) and Platelet Lymphocyte Ratio (PLR) as prognostic markers in ST-elevation Myocardial Infarction (STEMI) remains poorly researched. Aim: To determine the prognostic value of NLR and PLR to predict the immediate outcomes in patients with acute STEMI, and if any association exists between NLR/PLR and Thrombolysis in Myocardial Infarction (TIMI) risk score. Materials and Methods: This was a cross-sectional study conducted at a tertiary care centre, Puducherry, India, where 190 patients who presented to casualty with STEMI were enrolled. The patient co-morbidities, personal and family history were obtained. The routine laboratory parameters including platelets, lymphocytes, neutrophils and their corresponding ratios were calculated. Patients were grouped into low and high NLR/PLR groups and were assessed for occurrence of in-hospital mortality or Major Adverse Cardiovascular Events (MACE). Analysis was made to see if there is an association between NLR/PLR and MACE. Chi-square test and one-way ANOVA test was used for statistical significance. Results: Among 190 subjects, 157 male and 33 female with mean age of 55.72±11.24 years were included. A total of 8.94% patients 8.94% had MACE. NLR was positively associated with MACE (p-value=0.0006), whereas PLR was not associated with MACE. Patients with high NLR had 1.45 times higher odds of having MACE. NLR was significantly associated with TIMI risk score. Both NLR (F ratio=6.341) and PLR (F ratio=4.600) showed significant association with Killip classification, however NLR showed higher association (p-value <0.001). Conclusion: NLR can be used as a powerful prognostic marker for predicting immediate MACE and death in STEMI patients. In addition, NLR showed positive correlation with Killip classification and TIMI risk score.